California Democratic Presidential Delegation Committee Statement
This March 15, 1968 statement by Bob Coate, Northern Chairman of the Democratic State Central Committee, criticizes internal divisions within the California Democratic Party. Coate argues that Assembly Speaker Jesse Unruh's encouragement of Senator Robert F. Kennedy to enter the California presidential primary, coupled with attacks on President Johnson and Senator Eugene McCarthy, is divisive and harmful to party unity. He contends that Kennedy's entry would likely split anti-Johnson votes and indirectly benefit the Lynch delegation. While acknowledging McCarthy's courage in challenging Johnson, Coate warns that escalating intra-party conflict could weaken Democrats and aid Republican candidates in November. He urges Kennedy either to refrain from running or to ensure his candidacy does not contribute to Democratic defeat.